Disruptions of the olfactory and default mode networks in Alzheimer's disease. Issue 7 (4th June 2019) - Lu, Jiaming; Yang, Qing X.; Zhang, Han; Eslinger, Paul J.; Zhang, Xin; Wu, Sichu; Zhang, Bing; Zhu, Bin; Karunanayaka, Prasanna R.
Abstract: Introduction: Olfactory deficits are prevalent in early Alzheimer's disease (AD) and are predictive of progressive memory loss and dementia. However, direct neural evidence to relate AD neurodegeneration to deficits in olfaction and memory is limited. Methods: We combined the University of Pennsylvania Smell Identification Test (UPSIT) with olfactory functional magnetic resonance imaging (fMRI) to investigate links between neurodegeneration, the olfactory network (ON) and the default mode network (DMN) in AD. Results: Behaviorally, olfactory and memory scores showed a strong positive correlation in the study cohorts. During olfactory fMRI, the ON showed reduced task‐related activation and the DMN showed reduced task‐related suppression in mild cognitive impairment (MCI) and AD subjects compared to age‐matched cognitively normal subjects. Conclusions: The results provide in vivo evidence for selective vulnerability of ON and DMN in AD and significantly improves the viable clinical applications of olfactory testing. A network‐based approach, focusing on network integrity rather than focal pathology, seems beneficial to olfactory prediction of dementia in AD. Abstract : Olfactory and memory scores can differentiate Alzheimer's disease (AD) from mild cognitive impairment (MCI). Neurodegeneration, as measured by hippocampus and primary olfactory cortex (POC) volume is similar in AD and MCI. Patterns of ON activation support compensatory mechanisms in MCI and not in AD. DMN suppression during olfactory processing is impaired in AD. Effective connectivity between DMN and ON, in a model of causal influence, is impaired in AD.